2022
DOI: 10.1108/tr-02-2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

Digital accessibility of smart cities - tourism for all and reducing inequalities: Tourism Agenda 2030

Abstract: Purpose There is widespread agreement that the tourism sector should address the issue of sustainability. The purpose of this study is to analyze the digital accessibility of the cities awarded as European Capitals of Smart Tourism for their innovative, accessible and sustainable practices by the European Commission. Design/methodology/approach An analysis of the digital level of accessibility of 50 uniform resource locator (URL) of European cities was undertaken. The analysis followed the international eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…While automation can increase efficiency and productivity, it often fails to match human employees in terms of emotional engagement, communication, adaptability and friendliness (Stoyanova-Bozhkova et al , 2020). However, technology supports accessibility of destinations and all tourism and hospitality facilities (Fernández-Díaz et al , 2022). More widespread adoption of smart hospitality may also result in challenges for employees.…”
Section: Smart Hospitality Stakeholders: Reengineering Value Chains A...mentioning
confidence: 99%
“…While automation can increase efficiency and productivity, it often fails to match human employees in terms of emotional engagement, communication, adaptability and friendliness (Stoyanova-Bozhkova et al , 2020). However, technology supports accessibility of destinations and all tourism and hospitality facilities (Fernández-Díaz et al , 2022). More widespread adoption of smart hospitality may also result in challenges for employees.…”
Section: Smart Hospitality Stakeholders: Reengineering Value Chains A...mentioning
confidence: 99%
“…The destination accessibility factor is the ease with which a natural park can be reached by a community (Wang et al , 2015). In this context, accessibility relates solely to physical accessibility and its accompanying variables, including time, distance and cost (Celata, 2007; Fernández-Díaz et al , 2022). Other researchers have included additional physical accessibility variables, such as transportation modes and attractiveness (AlKahtani et al , 2015; Celata, 2007), variety of tour packages (Nyaupane and Graefe, 2008) and availability of tourism infrastructure (Toth and David, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The individual accessibility approach has been extensively employed when considering visitor accessibility. Individual accessibility evaluates a person’s level of desirability based on their needs, mobility, financial ability and time availability (Fernández-Díaz et al , 2022). Individual accessibility refers to a distinct personal background experience within a particular sociospatial environment (Lättman et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies related to bibliometric on COVID-19 (Dehghanbanadaki et al, 2020), studies on the person with disabilities experience during the current Pandemic (Epstein et al, 2021), including studies on government websites accessibilities, studied in several regional contexts, such as in Indonesia (Darmaputra et al, 2017), Saudi Arabia (Akram & Sulaiman, 2017), Latin America (Acosta et al, 2018), andDubai (Al Mourad &Kamoun, 2013). There is also similar research that studied the accessibility of the WHO website (Fernández-Díaz et al, 2020), but so far, we have found no research that responded to the needs of persons with disabilities by studying the accessibility of government websites that provide information on COVID-19, especially in countries with a relatively high case rate such as Indonesia.…”
Section: Introductionmentioning
confidence: 99%